The disruptive potential of the Massive Open Online Course: A literature review - Jean Jacoby (Flexible Learning Association of New Zealand, 2014)
The Massive Open Online Course (MOOC) is a rapidly evolving phenomenon which has stimulated discussion in universities around the world. A central theme of these discussions, and much of the published literature on the phenomenon, is the potential of the MOOC to disrupt the way universities do business. The aim of this narrative literature review is to clarify disruptive innovation theory, and to examine the influence of MOOCs on higher education. Evidence from this review suggests that although MOOCs might have had a significant effect on a range of issues (including definitions of completion pedagogical approaches, delivery methods, certification, and business models), more systematic research is needed to evaluate the level, extent, and permanence of any disruption that may occur.